Representations of the urban poor in Lino Brocka films - Isla, Veronica L. (2006)
This study focuses on how Lino Brocka represented the urban poor in his film texts and how his representations relate with his life, ideological beliefs, socio-historical milieu, and exposure to or association with local and/or foreign institutions, personalities, and artistic works. Using a humanistic approach drawn from two broad traditions, namely, phenomenology and hermeneutics, his representations are analyzed in terms of how expert and knowledgeable spectators (including the researcher) apprehend and experience his film texts, namely, Maynila sa mga Kuko ng Liwanag, Insiang, Jaguar, Bona and Bayan Ko: Kapit sa Patalim.His representations of the urban poor's environmental conditions, identity, way of life, and struggles were brought to the fore through a close examination of setting as well as narrative and character development. Since he had his own framework through which he understood, made sense and represented the urban poor, his representations necessarily included and excluded certain aspects of their reality. Moreover, although his life, experiences, and personality significantly relate with his representations, his cultural productions cannot be reduced to an essentially personal or psychological phenomenon since his way of being and thinking were also influenced by the prevailing cultural mood and trends that surrounded him. Certain socio-political realities motivated him to experiment with or combine a number of related, and even opposing representational strategies as long as these allowed him to achieve his purpose. The study reveals that his narrative and character construction closely adheres to the realist-naturalist tradition. This close adhere explains the varied and even contradictory reactions provoked by his discourse: while it is said that he represented social realities in a more radical manner, it is also said tha he obscured large social issues because his characters' struggles are on a personal and individual level. In other words, his strong realist-naturalist bent is both a strength and a weakness. While it led to the construction of characters that are unable to transcend their situation because of the pressure exerted by forces of environment, instinct, and passion, it allowed Brocka to present a biting critique of a social order that denies individuals viable means to realize their potential. Because of the latter, his discourse forms part of the struggle to undermine the establishment through cultural hegemony. Implicit in his realist-naturalist film texts is a reformist stance as he sought to expose social ills and to challenge the poor to reexamine themselves through inevitably tragic endings. Brocka's association with poetic realism, Italian neo-realism, and film noir is understandable since said film styles/movements are moderately or heavily influenced by realist-naturalist fiction. Brocka's close adherence to the core precepts of realism-naturalism allowed him to rise above prevailing cultural forms and usher in a new and pioneering discourse that redefined audiences' perception. However, his discourse is inescapably limited not only by his own perpective, but also by the very internal logic and conventions of realist-naturalist aesthetics. His film texts clearly implied but did not explore the complexity of the connection between charaters' specific situation and larger societal problems. Moreover, the implied societal problems are not linked to their deep structural causes. He individualized both societal problems and their causes. In short, his negative critique of the existing social order, though significant, is not sufficient.